Estimation of algorithm efficiency of the data array multiprocessing - Martyniuk, T. B.; Khomyuk, V. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The selection of coefficient of pair «structure-algorithm» co-ordination as criterion for the algorithm efficiency of the data array multisummation is grounded. The features of parallel multiprocessing algorithms , namely, algorithms of the logarithmic, recurrent summation and with using difference cuts are analysed.